User Satisfaction Analysis of the E-Monev Application Using the Integration of the EUCS and TAM Methods: A Case Study of the Jombang Regency Government - Mochamad Imamudin; Farhan, Ahmad; Kurniawan, Eddy (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2026)
The E-Monev application is used as a system for monitoring and evaluating program performance. However, based on preliminary field observations, it is found that some E-Monev users still experience various difficulties. Several commonly reported problems include an application interface that is considered difficult to understand, data access processes that are often slow and require a long time to load information, and confusion in operating the menus available in the E-Monev application. This study seeks to investigate user satisfaction and acceptance of the E-Monev application by combining two frameworks: the End User Computing Satisfaction (EUCS) and the Technology Acceptance Model (TAM). A quantitative approach was employed, involving the distribution of questionnaires to 134 E-Monev users within the Jombang Regency Government. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4. The analysis encompassed both the outer model assessing convergent validity, discriminant validity, and reliability and the inner model, which included evaluation of R-square, effect size, predictive relevance, and hypothesis testing.The results show that several variables, namely Content (t-value = 2.759; p-value = 0.006), Perceived Ease of Use (t-value = 3.637; p-value = 0.000), and Attitude (t-value = 14.965; p-value = 0.000), have a significant effect on the actual use of the application. Meanwhile, the variables of Accuracy, Perceived Usefulness, Ease of Use, Format, and Timeliness do not show a significant influence on user attitude. The factor with the strongest effect is Attitude toward Actual Use; therefore, enhancing users’ positive attitudes becomes the main key to optimizing E-Monev utilization. These findings provide insights for system administrators to improve content quality, ease of interaction, and user experience so that the implementation of E-Monev can be carried out more effectively.